2019
DOI: 10.1186/s12934-019-1086-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of leucine-responsive regulatory protein improves spiramycin and bitespiramycin biosynthesis

Abstract: Background Bitespiramycin (BT) is produced by recombinant spiramycin (SP) producing strain Streptomyces spiramyceticus harboring a heterologous 4″-O-isovaleryltransferase gene ( ist ). Exogenous l -Leucine ( l -Leu) could improve the production of BT. The orf2 gene found from the genomic sequence of S. spiramyceticus encodes a leucine-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…The resulting fermentation broth was extracted with ethyl acetate (100 mL), and the solvent was removed in vacuum. The extracts were dissolved in 1 mL CH 3 OH and centrifuged at 13,000g for 10 min, and 10 μL of supernatant was subjected to HPLC analysis following the previously described system [15]. In order to calculate the yields of carrimycin in the mutants and the starting strain 54IA, a quantitative curve was established based on the relationship of integral area and the weight of carrimycin.…”
Section: Genetic Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting fermentation broth was extracted with ethyl acetate (100 mL), and the solvent was removed in vacuum. The extracts were dissolved in 1 mL CH 3 OH and centrifuged at 13,000g for 10 min, and 10 μL of supernatant was subjected to HPLC analysis following the previously described system [15]. In order to calculate the yields of carrimycin in the mutants and the starting strain 54IA, a quantitative curve was established based on the relationship of integral area and the weight of carrimycin.…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…The titer of carrimycin was improved through the ribosome engineering, but it was far from the requirement in the scale-up fermentation. Many efforts have been made to improve the production of carrimycin in Streptomyces spiramyceticus WSJ−195 in recent years, including traditional random mutagenesis [9,10], medium optimization [11], exogenous feeding strategies [12,13], fermentation process control [14], and genetic engineering [15]. Among these approaches, traditional mutagenesis is a powerful and easily operated method for strain improvement in Streptomyces, especially for microbes with less understanding of genomic information and metabolic mechanisms.…”
mentioning
confidence: 99%
“…Exploring and optimizing polyketide biosynthesis can be completed within native production strains given that the BGC and necessary precursors are often already functionally expressed and produced. Typically, enhancing polyketide production focuses on the redirection and optimization of carbon flux via enhanced precursor availability [11,12], promoter and ribosome engineering [13], removal or overexpression of regulatory elements [14,15], deletion of competing biosynthetic pathways, and combinations thereof to significantly enhance titers above that of the wild-type pathway. Strategies including cooperative induction [9], co-culturing [16], and transcription factor decoys [17] have been explored for the activation of cryptic BGCs (cBGCs).…”
Section: Accessing Polyketides Via Host Strain Selection and Engineeringmentioning
confidence: 99%
“…Carrimycin (trade name: Bite, formerly shengjimycin and bitespiramycin), a new genetic engineering 16-membered macrolide antibiotic, is a mixture of isovalerylspiramycin I, II and III, and a certain amount of (iso)butyryl/propionyl/acetylspiramycin III and(iso)butyryl/propionyl/acetylspiramycin II ( Fig. 1 a) [6] . Completed phase III clinical trial showed an excellent anti-bacterial effect of carrimycin, as well as good bioavailability and high biosafety.…”
Section: Introductionmentioning
confidence: 99%